Methods of risk assessment in investment projects (Economics and region, 2024)
All forms and types of investment activity are inherently associated with an element of risk, the degree of which is contingent upon the evolution of market relations within the economy. In the contemporary era, the escalation of risk is contingent upon the instability and accelerated transformation of the economic milieu at the national level and within the investment sector. This encompasses the availability of privatised assets for investment, the advent of novel financial instruments, the emergence of new investment vehicles and a multitude of additional factors. Investment risk pertains to the potential for unforeseen financial losses (reduced profitability, income, capital erosion, etc.) in the context of uncertainty inherent to investment activities. The primary functions of investment management encompass a range of activities, including: the formulation of current forecasts and the planning of future activities; the identification of potential risk sources; the selection of appropriate management decisions aimed at eliminating or mitigating the impact of negative factors; the calculation of economic feasibility and the justification of proposed projects; the assurance of normal operations in the context of changing conditions; the determination of an acceptable level of risk; the development and implementation of measures designed to minimise the identified risks associated with a given project; the forecasting and modelling of relationships between factors; and the undertaking of complex analysis. The necessity to manage investment risks is contingent upon their existence. At present, a number of techniques are employed for the purpose of evaluating the degree of risk. A risk management method may be defined as a system of techniques or methods for performing individual operations within the risk management process. Nevertheless, the principal challenge lies in selecting the most suitable risk assessment approach, as each method possesses a distinct scope, along with inherent advantages and disadvantages. The main types of risk insurance in project finance are as follows: - Direct, which includes an unconditional guarantee of full payment from a guarantor with a sound financial position and cash security;- restrictions, including quantitative, time and other limitations. Simultaneously, project financing is beset with a number of challenges, including a dearth of local expertise in the development of large-scale projects, a paucity of qualified managers to oversee the data of individual entrepreneurs, insufficient resources for the large-scale financing of capital-intensive projects, the low qualifications of project financing participants, and the absence of a developed and legally approved mechanism for sharing risks between participants, among other factors that exacerbate project risks. The resolution of contemporary problems necessitates a multifaceted methodology that considers the interests of multiple stakeholders. The most crucial elements are the reinforcement of the state's role in guaranteeing project risk insurance, the provision of tax incentives for investment mechanisms, and the advancement of interbank collaboration in the domain of joint crediting of individual entrepreneurs. The article examined the classification of risks in investment projects, the methods of risk assessment and the minimisation of risks in investment projects.
Keywords: investment; project; risk; financing; forecast; method; dispersion; variation; mean square deviation; evaluation